What Women are Complaining About: Sexism on Campus - Abregana, Betty C. (Silliman Journal, 2022)
This article presents the various firms of sexism on campus based on a qualitative research done in four universities in central Philippines. As the research revealed, sexism is apparent in the teaching-learning activities in the classroom, behavioral interaction on campus, school policies and programs, co-curricular activities, and student services. The challenges for women’s studies are outlined and some initiatives to curb campus sexism are identified.